National postgraduate medical curriculum: enhancing anaesthesiology training in Malaysia - Md Ralib, Azrina; Md Hashim, Noorjahan Haneem; Shariffuddin, Ina Ismiarti (Malaysian Society of Anaesthesiology, 2023)
Postgraduate medical education in Malaysia started in 1973 with the launch of two clinical postgraduate programmes, Master of Psychological Medicine and Master of Pathology, by Universiti Malaya. Subsequently, the Government of Malaysia decided the responsibility for postgraduate medical education should rest with the universities, with the involvement of the Academy of Medicine of Malaysia (AMM) and the Ministry of Health (MOH). To date, Malaysian universities offer 23 postgraduate clinical programmes, including Master of Anaesthesiology. These programmes are conducted at individual universities, but in the spirit of uniformity, they are run in collaboration with all universities offering similar programmes as well as the AMM, and the MOH.